Poetry & translation the art of the impossible - Robinson, Peter 1953- (Liverpool University Press, 2010)
In Poetry & Translation the acclaimed poet and translator Peter Robinson examines the activity as of translation practised by poets and others, and how the various practices of translating have continued in parallel with the writing of original poetry. So, while some attention is paid to classic statements of the translators cultural role, statements such as Walter Benjamins, readers should not expect to find formalized theoretical debate along the lines already developed in translation studies courses and their teaching handbooks. Instead Poetry & Translation seeks to raise issues and matters for discussion - the character of bilingual editions and how they are, or may be, read - not to close them down. The aim of the book is be to increase knowledge of, and thought about, the interactive processes of reading and writing poetry composed in mother tongues and in translations. Poetry & Translation will be of value to all devoted readers and students of poetry or translation, to students involved in classical and modern languages, and to those taking part in creative writing courses, whether as students or as teachers
Title from publisher's bibliographic system (viewed on 02 Oct 2015)
Keywords: Poetry / Translating; Poetry / History and criticism; Lyrik; Lyriker; Muttersprache; Übersetzung